Constructive characteristics of some classes of smooth functions in two variables in the space C - Vishnjakov, M. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:М. В. Вишняков. Конструктивные характеристики некоторых классов гладких функций двух переменных в пространстве СM. Višniakovas. Kai kurių klasių glotnių dviejų kintamųjų funkcijų, priklausančių erdvei C, konstruktyvinės charakteristikos